Patient reported satisfaction following 1578 primary total knee arthroplasties in different ethnic groups in Leicester: are Caucasian patients more satisfied? - Suzangar, Mehdi; Esler, Colin; Kennedy, James; Chatterji, Urjit (International Journal of Research in Orthopaedics, 2018)
Background: Several non-UK and non-European studies, have suggested differences in post-operative outcome measures, including patient satisfaction, following total knee arthroplasty (TKA) when assessed against ethnicity. The aim of our study was to assess patient reported satisfaction following primary TKA in an ethnically diverse part of the UK, Leicestershire, to find out whether the Caucasian patients were more satisfied compared to non-Caucasians. Methods: Using our regional joint Registry, the Trent and Wales Arthroplasty Audit Group (TWAAG) registry, a retrospective analysis of the prospectively collected patients’ reported satisfaction following primary TKA was performed. 1578 patients from Leicester province who had undergone their first TKA in Leicester between 1990 and 2007, and who had responded to their 12 month validated post-operative questionnaires were included. Results: Overall patient reported satisfaction was 87.6%. Patient satisfaction was 87.7% in ‘British White’, 92.4% in ‘Other White’, 83.5% in ‘Indian/Pakistani’ population. When categorising patient ethnicity to ethnic groups, reported satisfaction was 88.1% in the ‘Caucasian’ group and 83.4% in the ‘non-Caucasian’ groups. Fisher’s exact test did not indicate a statistically significant difference in the reported satisfaction between these ethnic groups. Conclusions:In our study, ethnicity was not a significant attributing factor in patient reported satisfaction following primary TKA.